10 Years of Experience in Carbon Finance : Insights from Working with the Kyoto Mechanisms - World Bank (Washington, DC: World Bank, 2012)
Under the Kyoto Protocol to the United Nations Framework Convention on Climate Change (UNFCCC), the industrialized countries adopted quantified emission reductions obligations. Marking the 10th anniversary of the establishment of the World Bank Prototype Carbon Fund (PCF) the world's first global carbon fund, this report seeks to take stock of the World Bank's experience of working with the Kyoto Protocol's project-based mechanisms over the past decade. The Clean Development Mechanism (CDM), as the much larger system in terms of projects, emission reductions and host countries, is the basis for much of the report's discussion. Joint Implementation (JI) is also discussed. Policy-makers and negotiators are working on advancing the policy framework and the regulatory structures to mitigate greenhouse gas (GHGs) at greater scale. Furthering the use of market instruments should incorporate the lessons of the past into future designs, making full use of the experience and learning that has been gained. This will mean building upon the successes of the current CDM and JI regulatory frameworks, addressing weaknesses, and abandoning what is not working. This publication seeks to make a constructive contribution to this debate, in full respect of the ongoing international climate change negotiations, by providing insights and recommendations from a practitioner's experience and perspective.